“CONSTANT, ZIG-ZAG LINEAR, OR MULTIPLE?”: THEMATIC PROGRESSION PATTERNS ON EFL STUDENTS’ RECOUNT TEXTS - Merina Devira; Makhroji Makhroji; Allif Syahputra Bania; Novia Sari (UIN Alauddin Makassar, 2020)
The main problem faced by EFL students in writing English texts includes the difficulties to produce a cohesive and coherent text that it seems necessary to show how the tools of Theme and Rheme can be used to help construct the students' good English writing. This study aimed to find out the types of thematic progression patterns in each clause of the recount texts written by students and the dominant pattern of thematic progression revealed from the texts. The research design of this study is a qualitative method which employed the study instrument of the students' recount texts at class IX of SMAN 2 Langsa, Aceh. A content analysis approach by using a Theme and Rheme framework generated from a theory of Systemic Functional Linguistics (SFL) was used to analyze the thematic progression patterns on the students' recount texts, which included several steps: reading the student's texts, identifying the theme and rheme of every clause of the student's text, describing the thematic progression patterns of student's text and drawing the thematic progression pattern on student's text. The findings of the analysis indicated that there are three (3) thematic progression patterns found on the students' recount texts: the Theme Constant, the Theme Zig Zag Linear pattern and Theme Multiple patterns. The dominant type of thematic progression patterns constructed by the students into their recount texts was revealed mostly on 123 constant or reiteration patterns (76.8%), followed by zig-zag patterns of 35 times (21.8%) and 9 times (1.25%) of multiple patterns. The results of this study will be facilitative as the tools for English language teaching and learning classrooms particularly for writing English texts.